Silverlight 2 in action - Campbell, Chad A. (Manning, 2009)
"Silverlight 2 in Action is the first book to cover Silverlight 2, a far more robust implementation of Silverlight than the current 1 release that supports only JavaScript. The much-anticipated 2 release adds powerful new features along with the ability to code in multiple languages and integrate your work with Visual Studio and the new Expression suite of tools. This book delivers real-world examples and in-depth walkthroughs to help you confidently enhance your web applications using Silverlight 2." "Silverlight 2 in Action devotes extensive coverage to flexible layout components, the extensible control model, the communication framework, and the data-binding features - all cornerstones of software development. Author and Microsoft MVP Chad Campbell also describes rich media and vivid graphical and animation features. The final chapters include a variety of Silverlight deployment scenarios."--Jacket
Includes index. - Title from resource description page. - Print version record
Keywords: Silverlight (Electronic resource); Multimedia systems; Web sites -- Design; Application software -- Development; Multimédia; Sites Web; Conception; Logiciels d'application; Développement; Web sites; Design; Application software; Development